Seed rain in a restoration site and in an adjacent remnant of Seasonal Atlantic Forest - Vindica, Vanessa França (2020)
Ecological succession depends on the seed rain. While the simple arrival of seeds is not assurance of establishment, knowing the seed rain is the first approach to assessing the succession process in sites undergoing forest restoration. For this reason, we sampled the seed rain in a restoration site and in an adjacent seasonal semi-deciduous forest remnant in southern Brazil, in order to describe the process. In each area, 18 seed traps (1 m2) were allocated and visited monthly for two years. All seeds trapped were identified, counted and classified by life form, ecological group and dispersal syndrome. The forest remnant presented higher species richness and abundance of propagules than the restoration site. The composition of species also differed between areas. The seed rain of both areas presented a higher proportion of tree and shade-intolerant species. Several non-planted species, possibly dispersed from forest remnant, were recorded in the restoration site. Analysis of the results suggests that the seed rain is not a constraint to succession in the restoration site. However, the site should be monitored in the long term to assess the establishment, and not only the arrival of seeds of late successional species.